Marked Cofuel Tuning of Combustion Synthesis Pathways for Metal Oxide Semiconductor Films. (23rd July 2019) - Wang, Binghao; Leonardi, Matthew J.; Huang, Wei; Chen, Yao; Zeng, Li; Eckstein, Brian J.; Marks, Tobin J.; Facchetti, Antonio
Abstract: Thin‐film combustion synthesis (CS), driven by the exothermic reaction of liquid fuel+oxidizer+metal precursors is an important methodology for growing smooth, transparent, amorphous, and polycrystalline metal oxide (MO) films at low temperatures. In optimized MO CS precursors, the fuel combines a primary coordinating ligand [e.g., acetylacetone (AcAcH)] with an additional cofuel. Several studies suggest a structure–property relationship between the resulting MO film composition/microstructure and macroscopic charge transport characteristics. However, the structural and compositional details of solution‐phase precursors remain poorly defined. Here a diverse series of cofuels (urea, glycine, sorbitol, L ‐ascorbic acid) are selected and mechanistic details of the fuel‐assisted CS process are provided, focusing on technologically relevant indium gallium zinc oxide (IGZO). Thermal analysis, proton nuclear magnetic resonance, mass spectrometry, and X‐ray diffraction are used to probe how the cofuel affects AcAcH‐metal ion binding and how it influences the MO precursor response. The charge transport characteristics of cofuel‐derived IGZO films stimulate additional cofuel studies and the results support the primary cofuel role of enhancing CS heat generation, hence IGZO film microstructure densification and carrier mobility. These results provide new insight into precursor design and its relationship to thin‐film CS processes, yielding guidance for more efficient, environmentally benign (co)fuels for high‐performance solution‐processed MO electronics. Abstract : The mechanism of fuel‐assisted combustion chemistry of indium gallium zinc oxide (IGZO) film growth is investigated using chemically different cofuels, with comprehensive thermal, structural, and coordination chemistry analysis of the cofuels and IGZO precursors in solution and in the solid state. The use of the cofuels affects AcAcH‐metal ion coordination and, consequently, the IGZO films' electronic/microstructure properties and charge transport.